Lexicon for sensory evaluation of tactile textiles in Brazil - Nagamatsu, Rosimeiri Naomi (2016)
The space between clothing and the body is related to users comfort. Due to the priority to protect man from a particular hazard, the interaction between clothing and body comfort as well as structural properties of materials to be used in clothing manufacturing is often neglected. Indeed, comfort is one of the most important properties that influence the users decision when choosing a particular piece of clothing. Touch is one of the most used practice by the consumer to verify the comfort of the fabric. Thus, the touch is a tool to assess the quality of high sensitivity fabrics. Investigations were carried out in France and Portugal in order to quantify the quality of touch textiles. The researchers used the sensory analysis method much exploited by the food industry and cosmetics and developed lexicons for tactile sensory evaluation in textiles. The development of a lexicon for tactile sensory analysis is an important tool for tactile evaluation of products. For its development a selection of samples representing the product is performed and the development of protocols to be followed systematically by evaluators generate the terms and quantitative or qualitative validation. Thus, this article presents the procedures used for the development of the Brazilian textile lexicon.